KETERAMPILAN SAINS ANAK USIA 4-5 TAHUN DALAM PEMBELAJARANBERBASIS SENTRA DAN LINGKARAN DI TK ANDIKA KOTA CILEGON BANTEN - Rini Wahyuni (Early Childhood Teacher Education Department UNIVERSITAS SULTAN AGENG TIRTAYASA, 2016)
Learning in TK basically adopts learn while playing and playing while learning. Applying the method based learning centers and circles, the process of learning activities that children do become more purposeful and fun through 4 kinds foothold in the center so that put children in a position proportional to stimulate the development and skills of children properly. But in reality there are many institutions early childhood that still uses a classical system that is less oriented to the development and parenting skills, learning focused on the end result to be achieved without promoting the process through which the child when learning activities, so that learning look monotonous and development as well as parenting skills lacking stimulated properly. Science skills or the process of doing science for young children to play an important role in life for children, both in the present and for the future. With science skills are stimulated properly, the child will acquire skills in critical thinking, problem solving, gain knowledge and scientific information. In early childhood science skills can be stimulated through the learning is done every day in the center and a circle. This study aims to: 1) to find out how the teacher’s role in stimulating science skills of children, 2) to find out how the learning process of children in centers and circles, 3) to find out what science skills of children that occur during the process of learning activities in the center and circle, 4) to determine the factors supporting and inhibiting factors science skills of children in the center and a circle. This research uses descriptive method with qualitative approach. The subjects of this study are children aged 4-5 years in TK Andika. Data is collected using the method of observation, interviews, documentation, and field notes. The researcher is the main instrument for doing research assisted by guidelines for observation, interview, and documentation guidelines.